Handbook of surface treatments and coatings - Cartier, Michel; Curtis, J.M; Polak, T.A; Wilcox, G.D (Tribology in practice series, 2003)
Contains information for the selection and appropriate use of surface treatments and coatings in mechanical engineering. This book covers topics such as: elements of surface mechanics; parameters and definitions; principal phenomena or surface transformation and wear; the role of surface treatments; and properties and applications